Fabricando patrimônios: a UNESCO como arena de reconhecimento - Marina Mafra Garcia (e-cadernos ces)
This paper seeks to extend the knowledge on UNESCO’s policies for the safeguarding and promotion of intangible cultural heritage. The idea is to promote a deeper analysis of UNESCO’s “institutional culture”, focusing on the examination of this distinct institutional universe, with its specific values and interests. The goal is to reflect on the manner through which this institution attempts to universally legitimate the requirements of diversity and cultural persistence as basic essential principles that every society must respect. What are the strategies, the practices, the relationship networks and the worldviews that make the emergence of this new order of cultural legitimacy possible? How do UNESCO’s policies of patrimonialization work as mechanisms of power, affirmation and recognition?